Exploring the Interplay Between Economic Benefits, Social Challenges, and Sustainable Tourism in Chiang Mai and Phuket - Nawat, Renta; Phongsavath, Thanaporn; Srisuk, Chirathiwat; Suwanan, Sakda (Journal of Humanities and Social Sciences (JHASS), 2024)
This study investigates the impact of tourism on local communities in Chiang Mai and Phuket, Thailand, focusing on the socio-economic, cultural, and environmental dimensions. A mixed-methods approach was used, combining qualitative interviews with local business owners, tour guides, and residents, alongside quantitative surveys from 50 tourists in each region. Chiang Mai, known for its cultural heritage, and Phuket, a major beach tourism destination, offer contrasting tourism experiences, making them ideal case studies. Data was collected from February 2023 to February 2024, with findings revealing significant impacts on local economies, culture, and environmental sustainability. In Chiang Mai, cultural preservation efforts are challenged by over-tourism, whereas Phuket faces severe environmental degradation due to mass tourism. Both regions highlight the importance of sustainable tourism practices. The study also identifies opportunities in digitalization for promoting local tourism and the need for educational programs for both tourists and residents to enhance sustainability awareness. Future research could explore deeper into the effectiveness of digital tools for local tourism promotion, the integration of community-based tourism strategies, and the role of government policies in promoting sustainability in tourism. Understanding these dynamics will contribute to more inclusive and sustainable tourism practices in Thailand and other similar destinations.